Pengembangan Geowisata dan Perubahan Sosial-Budaya Masyarakat di Area Geopark Ciletuh-Palabuhanratu - Syafira Ayudarechta Tara Wendita (Universitas Padjadjaran, 2019)
Ciletuh-Palabuhanratu Geopark has been inaugurated as the first global geopark in the West Java Province in April 2018. Since 2002, geotourism is the development model being chosen by the geopark management to popularize this geopark. This study aims at describing the influence of geotourism development on socio-cultural changes in people who live in the Ciletuh-Palabuhanratu Geopark. This study uses qualitative methods in particular case study. Primary data collection include in-depth interviews and participant observation and secondary data was collected through archival studies. This study finds indications the socio-cultural changes of the communities living at the geopark area along with the development of geotourism. There is a change in the livelihoods form among the community members from peasant and fishermen to tourism businessmen. There is also a growing of local organizations working on tourism management, revitalization of local traditional arts for tourism commodities, and the emergence of new patterns of social interaction between local communities and tourists.